2013
DOI: 10.5902/198050988458
|View full text |Cite
|
Sign up to set email alerts
|

<i>Qualea grandiflora</i> Mart.: temperatura na germinabilidade de sementes

Abstract: Qualea grandiflora Mart. ocorre em matas de galeria e cerrado, sendo conhecida popularmente como pauterra. Com o objetivo de obter informações sobre a propagação reprodutiva dessa espécie foi estudado o efeito da temperatura sobre a germinabilidade das sementes. As temperaturas utilizadas foram: 15, 20, 25, 30, 35 e 40 ºC. As sementes foram semeadas em substrato papel-toalha, na forma de rolo, com quatro repetições, sendo a unidade experimental constituída por um rolo com 25 sementes. O experimento seguiu o de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The temperatures of 15 and 30 °C were lower compared to the other temperatures tested, as observed for G. The low development of seedlings of these cultivars in extreme temperatures can be explained as a selection of biological nature, which prevents the development of the species in unsuitable environments (Bilio, Guimarães and Caldeira;.…”
Section: Test II -Temperature During Germination and Seed Vigor Testsmentioning
confidence: 71%
“…The temperatures of 15 and 30 °C were lower compared to the other temperatures tested, as observed for G. The low development of seedlings of these cultivars in extreme temperatures can be explained as a selection of biological nature, which prevents the development of the species in unsuitable environments (Bilio, Guimarães and Caldeira;.…”
Section: Test II -Temperature During Germination and Seed Vigor Testsmentioning
confidence: 71%
“…(Rosseto et al, 2009), Qualea grandiflora Mart. (Bilio et al, 2013) and Theobroma grandiflorum (Willd. ex Spreng.)…”
Section: Discussionmentioning
confidence: 99%
“…This resistance to high temperatures is necessary because of the occurrence of air and soil surface temperatures of up to 350 °C during fire, depending on the fuel load (Miranda et al 1993). However, fire can also promote germination by breaking seed dormancy (Bilio et al 2013, Ribeiro & Borghetti 2014. The observed seed attributes and seed mass, therefore, increase seeds' tolerance to environmental stress and are likely to contribute to the recruitment of the tree species in the harsh environments of the cerrado (Bond & Keeley 2005, Ribeiro & Borghetti 2014.…”
Section: Seed Storagementioning
confidence: 99%
“…Ribeiro & Borghetti (2014) demonstrated the great tolerance of Q. grandiflora seeds to extremely high temperatures and desiccation, achieving high germination rates of 63% to 71%. Experimental studies by Bilio et al (2013) and Dousseau et al (2013) showed that temperatures of 25 to 30 °C lead to the highest germination rates under controlled conditions, irrespective of the presence or absence of light (Zaidan & Carreira 2008). In order to survive, seedlings must develop deep roots before the next dry season starts (Rizzini 1965, Salazar 2010.…”
Section: Germination and Development Of Early Seedling Stagesmentioning
confidence: 99%